2017
DOI: 10.18632/oncotarget.17096
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces G2/M cell cycle arrest and apoptosis of head and neck squamous cell carcinomain vitroandin vivothrough ATM/Chk2/p53-dependent pathway

Abstract: Studies have demonstrated that curcumin (CUR) exerts its tumor suppressor function in a variety of human cancers including head and neck squamous cell carcinoma (HNSCC). However, the exact underlying molecular mechanisms remain obscure. Here, we aim to test whether CUR affects ATM/Chk2/p53 signaling pathway, leading to the induction of cell cycle arrest, inhibition of angiogenesis of HNSCC in vitro and in vivo. To this end, we conducted multiple methods such as MTT assay, Invasion assay, Flow cytometry, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 47 publications
2
22
0
1
Order By: Relevance
“…In this study, the cell cycle analysis was carried out for PAN02 pancreatic cancer cells after treating with free TOS, curcumin, and TOS/curcumin-loaded micelles for 48 h. As shown in Figure 5 b, PAN02 cells treated with free TOS and TOS + free curcumin showed a higher accumulation of cells in the G0G1, while TOS and or curcumin-loaded micelles showed cell inhibition at the G2M phase compared to that of the untreated PAN02 pancreatic cancer cells. A similar observation was observed that showed curcumin-mediated cell cycle arrest at G0G1 and G2M checkpoints [ 43 ].…”
Section: Resultssupporting
confidence: 84%
“…In this study, the cell cycle analysis was carried out for PAN02 pancreatic cancer cells after treating with free TOS, curcumin, and TOS/curcumin-loaded micelles for 48 h. As shown in Figure 5 b, PAN02 cells treated with free TOS and TOS + free curcumin showed a higher accumulation of cells in the G0G1, while TOS and or curcumin-loaded micelles showed cell inhibition at the G2M phase compared to that of the untreated PAN02 pancreatic cancer cells. A similar observation was observed that showed curcumin-mediated cell cycle arrest at G0G1 and G2M checkpoints [ 43 ].…”
Section: Resultssupporting
confidence: 84%
“…CHK2 is regulated by ATM after DNA double strand breaks and participates in the checkpoint regulation by phosphorylating CDC25C-Ser216. Compared with ATR-CHK1, ATM-CHK2 aims to provide a rapid protective response to DNA damage in cells [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has been found to be biologically active against a variety of tumour types. It induces G2/M cell cycle arrest of head and neck squamous cell carcinoma and in colorectal cancer (Hu et al 2017, Jaiswal et al 2002. Curcumin has also been found to inhibit the growth of two pancreatic cancers cell lines in a dose-and time-dependent manner (Zhu and Bu 2017).…”
Section: Resultsmentioning
confidence: 99%